Analisa Kinerja Simpang 4 Tak Bersinyal Jl. Tambak Mayor Utara-Jl. Dupak Rukun-Jl. Asem Mulya Surabaya - Mohammad Iqbal; Nurani Hartatik; Laily Endah Fatmawati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Roads are transportation insfrastructure that include all parts of the roads, including complementary buildings and equipment intended for traffic. Surabayais located and serves as the capital of East Java Province, With a  Population reaching 3,043 milion people’s in 2025 based on data from the Surabaya City Population and Civil Registration Office. Based on this topic, it is necessary to conduct a re-evaluation be analyzing the performance of an unsignalized four-way intersection using PKJI 2023. The research location  in on Dupak Rukun Street Surabaya, Focusing on intersection performance, using the manual traffic recording survey method. After observation and data analysis, it was found that the degree of saturation (DS) in the initial calculation was 0,8566, which falls into the congested category and causes traffic jams. Then, several adjustment were made by increasing the width oh the minor approach lanes from 6 to 7 meters and the major roads form 8 to 10 and 11 meters, resulting in a DS value of 0,8133.